Stiff-person syndrome in association with Hashimoto’s thyroiditis: a case report - Chen, Mingzhu; Hong, Zhou; Shi, Haicun; Wen, Chunmei; Shen, Yuan (Frontiers in Neurology, 2024)
Stiff-person syndrome (SPS) is a rare neurological disorder characterized by chronic and progressive axial muscle rigidity and paroxysmal painful muscle spasms. The present case study described an SPS patient (increased anti-GAD65 antibody in serum and cerebrospinal fluid) with co-occurring Hashimoto’s thyroiditis and decreased C3 complement levels. The clinical presentation, diagnostic approach, and treatment employed for this unique case were comprehensively described in detail. In this case, we comprehensively presented a case of SPS with co-occurring Hashimoto’s thyroiditis and an associated decrease in serum C3 complement, as well as a discussion on the current data on this topic.